Determinants of non-cardiorespiratory fitness in pre-elderly women - Mustakim Mustakim; Kusharisupeni Djokosujono (Alma Ata University Press, 2019)
ABSTRAK Latar Belakang: Kelompok lanjut usia mengalami perkembangan yang pesat di masa mendatang. Kebugaran menjadi salah satu prediktor dalam menentukan kesakitan dan kematian pada kelompok lansia.Tujuan: Penelitian ini memiliki tujuan untuk membahas karakteristik, komposisi tubuh, gaya hidup dan asupan gizi dengan kebugaran yang diukur melalui serangkaian tes kebugaran pada wanita pralansia di Kecamatan Pancoran Mas kota Depok.Metode: Penelitian menggunakan desain studi cross-sectional dan dilakukan pada 134 orang wanita pralansia di Kecamatan Pancoran Mas kota Depok.Hasil: Hasil penelitian menunjukkan bahwa 72,4 persen wanita pralansia berada pada kondisi tidak bugar. Variabel paling berhubungan dengan kebugaran adalah aktivitas fisik setelah dikontrol dengan IMT, persen lemak tubuh, status merokok dan asupan vitamin B12.Kesimpulan: Akivitas fisik merupakan faktor paling berpengaruh terhadap kebugaran non kardiorespiratori pada wanita pralansia. Oleh karena itu, wanita pralansia wajib menjaga aktivitas fisiknya secara rutin melalui jalan kaki, senam ataupun kegiatan fisik lainnya.KATA KUNCI: wanita pra lansia, kebugaran non kardiorespiratori, aktivitas fisik ABSTRACTBackgrounds: Fitness was found as an indicator of morbidity and mortality to the elderly. A person who have low physical fitness level is often associated with a lack of regular physical activities and causes of degenerative diseases and premature death. Besides, fitness will have an inluenfce to his body composition (reduced fat levels in the abdomen), increase lipid profile (reduced triglyceride levels, increased HDL), reduce LDL, and reduce blood pressure.Objectives: This study focused on the physical fitness of middle-aged women in Pancoran Mas, Depok. The purpose of this study was to look at the relationship between lifestyle, body composition and nutritional intake and physical fitness. In addition, this study also determined the dominant factor related to physical fitness.Methods: This study used a cross-sectional design and the data were collected from 134 middle-aged women. Physical Fitness was measured by fitness test using handgrip test, sit and reach test, and chair sit and stand the test. Data on body composition will be collected through a series of anthropometric measurements. Meanwhile, nutrition intake was collected using an interview questionnaire on a 2-day 24-hour dietary recall and lifestyle were collected by using Physical Activity Scele for Elderly (PASE Questionnaire).Results: The result showed that 72.4 percent of respondents had a low category level condition. This study showed that there is a significant relationship between physical activities and non-cardiorespiratory fitness in middle-aged women. The dominant factor related to determining fitness was physical activities with OR 2.382 after being measured by a percentage of body fat, body mass index (BMI), smoking status and vitamin B12 intake.Conclusions: The most influential variable was physical activities after adjusted by BMI (Body Mass Index), the percentage of body fat, smoking status, and vitamin B12 intake.middle aged women should keep their physical activity in active level. They can use walking or aerobic dance to maintain their physical activity.KEYWORDS: Middle-aged women; non-cardiorespiratory fitness; physical activity